Peran Kelompok Tani Kamba Ula Dan Tingkatan Kesejahteraan Petani Di Desa Dumoga Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Yudha, I Nengah Harta; Ngangi, Charles Reijnaldo; Pangemanan, Lyndon Reindhart Jacob (AGRI-SOSIOEKONOMI, 2023)
This study aims to determine the role of farmer groups in improving the welfare of farmers in Dumoga Village, East Dumoga District. This research was conducted from August to December 2022 in Dumoga Village, East Dumoga Subdistrict, Bolaang Mongondow Regency, North Sulawesi Province. The research used primary data obtained through distributing questionnaires directly to corn farmers in Dumoga Village, East Dumoga Subdistrict, Bolaang Mongondow Regency, while Secondary data were obtained from simultaneous reports in Dumoga Village, East Dumoga Subdistrict, Bolaang Mongondow Regency. The sampling method uses a total sampling method of 25 samples from the total population. The samples taken were corn farmer groups that produced in 2022. The data analysis method used in this research is descriptive analysis method. Descriptive analysis is to explain and describe the state of phenomena that occur in the research area and to determine the role of farmer groups in improving the welfare of corn farmers. Furthermore, descriptive analysis measurements were carried out using a Likert scale, then scored, namely Score 1: Disagree, Score 2: Disagree, Score 3: Agree, Score 4: Strongly Agree. The results showed that the role of the Kamba Ula Farmer Group was very instrumental, both its role as a learning class, a vehicle for cooperation and a production unit played a role in this, so the level of farmer welfare increased because of the role of the farmer group had provided counseling and assistance.